Cohort study of the depression, anxiety, and anhedonia components of the Edinburgh Postnatal Depression Scale after delivery. Issue 3 (22nd March 2017) - Zanardo, Vincenzo; Giliberti, Lara; Volpe, Francesca; Parotto, Matteo; de Luca, Federico; Straface, Gianluca
Abstract: Objective: To investigate the applicability of the Edinburgh Postnatal Depression Scale (EPDS) for identifying depressive symptoms following vaginal or cesarean delivery. Methods: The present observational study included consecutive Italian‐speaking women who underwent vaginal or cesarean deliveries of uncomplicated singleton pregnancies at term at Policlinico Abano Terme, Abano Terme, Italy, between February 1, 2014, and May 31, 2015, who completed the EPDS 2 days after delivery. EPDS scores and the depression, anxiety, and anhedonia subscale items were compared between delivery methods to identify factors predictive of high EPDS scores. Results: There were 950 patients included in the analysis; 694 (73.1%) and 256 (26.9%) patients underwent vaginal and cesarean deliveries, respectively. Total EPDS scores were higher among patients who had cesarean deliveries compared with vaginal deliveries (6.95±4.80 vs 6.05±4.20; P =0.007); the depression (0.53±0.72 vs 0.37±0.65; P =0.007), anxiety (1.07±0.88 vs 1.16±0.93; P =0.021), and anhedonia (0.32±0.59 vs 0.19±0.48; P =0.009) subscale scores were all higher among patients who underwent cesarean deliveries. Conclusion: Women who underwent cesarean deliveries demonstrated higher EPDS scores and could be at increased risk of developing early postpartum depressive symptomatology, particularly anhedonia, anxiety, and depression. Abstract : Higher total EPDS and subscale scores were recorded among patients who had cesarean deliveries. EPDS subscales represent a good tool in understanding postpartum psychological disorders.